Peran Badan Permusyawaratan Desa Dalam Meningkatkan Efetivitas Pemerintahan di Desa Koreng Kecamatan Tareran Kabupaten Minahasa Selatan - Kawung, Noffy (Sam Ratulangi University, 2015)
Abstract: The conception of the village as Consultative Bodies that are desired by Act No. 22 of 1999 is toprovide powerful control functions to the village chief in addition, Consultative bodies of the village isknown for the introduction of the legislative Institutions, and have the authority the authority legislationgenerally in the village. The quality of human resources (public), including the village governmentapparatus and Leadership as well as members of the Village institutions in the improvement of theeffectiveness of implementation of giliranya inhibits the Government village, so there is also an impact onthe effectiveness of Implementation the Government accelerated the slow pace of the village itself.Konstalasi that causes BPD do not proactively with his duties because of the factor of human resources(HR) members. Based on explanation above, the authors are encouraged to conduct research on thesystem of Government with the title role of the Consultative bodies of the village of Efetivitas in improvinggovernance at the village of Tareran Sub-district Koreng South Minahasa Regency.This research uses qualitative research methods deskriptis with the data analysis techniques,described in the form of description sentences by giving interpretation/interpretation based on directinterviews conducted with a sample of existing research object or the respondent is there, so it can be usedby way of presentation techniquesThe research results and conclusions stated that perluanya there is a good relationship between BPDand the Government of the village, an increase in the Metal of the BPD was also in a sense quitenecessary, in order that they may be liable with all their duties and responsibilities.Referring to the conclusions above, in order that the Government shall recommend to hold specialtraining to BPD so that in carrying out tasks they can optimally, it needs also the existence of arelationship between the Government of the village and a tub of BPD as a partner.